2013
DOI: 10.4238/2013.november.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of marker genes in diabetic wounds by DNA microarray study

Abstract: ABSTRACT. This study aimed to identify marker genes in diabetic wounds using a dataset based on a DNA microarray of dermal lymphatic endothelial cells, and our results provide a basic understanding of diabetic wounds through further study of these differentially expressed genes (DEGs). From the Gene Expression Omnibus database, we downloaded a gene expression microarray (GSE38396) that includes 8 samples: 4 normal controls and 4 disease samples (type II diabetes). We then identified genes that were differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Studies have used microarrays to detect genetic contributors to diabetes-impaired wound healing. Consequently, several relevant genes such as CD44 , CCL5 , and IL-6 [ 21 , 22 ]—which play vital structural and functional roles in the regulation of diabetic wound progression—have been identified. Based on transcriptomic microarray data from DFUs and nondiabetic foot skin samples and subsequent DEG identification and GO and KEGG enrichment analyses, we identified EGFR as a potentially critical player in delayed wound healing in DFUs.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have used microarrays to detect genetic contributors to diabetes-impaired wound healing. Consequently, several relevant genes such as CD44 , CCL5 , and IL-6 [ 21 , 22 ]—which play vital structural and functional roles in the regulation of diabetic wound progression—have been identified. Based on transcriptomic microarray data from DFUs and nondiabetic foot skin samples and subsequent DEG identification and GO and KEGG enrichment analyses, we identified EGFR as a potentially critical player in delayed wound healing in DFUs.…”
Section: Resultsmentioning
confidence: 99%
“…Shao et al [13] identified that the glucocorticoid was central in the pathogenesis of type 2 diabetes from three GEO datasets by integrated method including DEGs screen, gene functional enrichment, PPI network analyses, drug–gene interactions and genetic association of DEGs. Ni et al [14] identified key genes in the diabetic wounds from one GEO dataset using a bioinformatics approach incorporating DEG screen, PPI network and phylogenetic analysis. Chen et al [15] used the gene expression profiles from GEO datasets and identified candidate genes for type 2 diabetes and obesity by screening of genes, GO and pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the gene expression changes’ role in diabetic complications might provide novel insights into the genome function mechanisms in T2D, making it possible to define the risk groups for a severe course of disease and to prevent its microvascular and macrovascular complications. The CD44 and CCL5 genes were found to be associated with wound healing in diabetic patients when analyzing the transcriptome of dermal lymphatic endothelial cells [ 79 ]. CCL5 is a chemokine that is a chemoattractant for inflammatory cells that release pro-angiogenic factors, stimulating wound vascularization [ 80 ].…”
Section: Transcriptome Studies In T2dmentioning
confidence: 99%